PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN COOPERTIVE TIPE TEAM PAIR SOLO - efendy, rustam (azkiya, 2019)
This study aims to improve the learning outcomes of science students of class VI by applying the Solo Team Pair Type Cooperative Model (TPS). This type of research is the Hopkins model PTK. This research was carried out collaboratively with colleagues to create better learning outcomes. The study was conducted in 2 (two) cycles and each cycle was conducted 2 (two) meetings. The subjects in this study were class VI students totaling 26 people. The data collection techniques used were observation sheets and written tests. The data analysis technique used in this study is qualitative descriptive. The results showed that with the application of the Solo Team Pair Type Cooperative Model (TPS) in the first cycle the average value on the learning outcomes test was 69.04 with learning completeness in the classical amounting to (57.69%) In the second cycle the learning outcomes were increased the average value of students is 80.38 with classical learning completeness reaching (96.15%). Thus it was concluded that the application of the Solo Team Pair Type Cooperative Model (TPS) through the stages of stimulation, problem formulation, data collection, data analysis, verification, and generalization can improve the IPA material science learning outcomes for class VI